Ecological consciousness and ecosophical participation in Ki. Rajanarayanan’s Pinjugal - Prabhu, M.S Siddharth; Sam, D Praveen (Research Journal in Advanced Humanities, 2026)
Ecocriticism, as an interdisciplinary field, seeks to understand the intricate connections between humankind and the biosphere as represented in literature and other cultural artifacts. It ultimately calls for a shift from human-centric lifestyles toward ecological harmony. Rooted in textual analysis and theoretical synthesis, the present study draws on insights from ecocriticism and its allied fields – ecosophy and ecofeminism – to examine the ecological consciousness expressed in Pinjugal (1979), a Tamil children’s novella by the acclaimed writer Ki. Rajanarayanan. The analysis interprets the value of nonhuman entities—particularly the rural landscape and its life-forms—that gradually guide the young protagonist Venkatesu (a dropout schoolboy) toward active ecological participation and ultimately towards eco-wisdom. The study also explores the eco-ethics held by the characters (though marked by inherent contradictions) that demonstrate their heightened awareness of the natural world. Pinjugal is thus posed as a testament to the potential of indigenous children’s literature to instill eco-ethics and sustainable living.